2019
DOI: 10.3390/agronomy9040192
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal Biostimulants and Biofertilisers in Crop Productions

Abstract: Microalgae are attracting the interest of agrochemical industries and farmers, due to their biostimulant and biofertiliser properties. Microalgal biostimulants (MBS) and biofertilisers (MBF) might be used in crop production to increase agricultural sustainability. Biostimulants are products derived from organic material that, applied in small quantities, are able to stimulate the growth and development of several crops under both optimal and stressful conditions. Biofertilisers are products containing living m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
245
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(263 citation statements)
references
References 153 publications
(196 reference statements)
5
245
0
13
Order By: Relevance
“…Previous studies have shown that algal extracts and their purified compounds can induce strong physiological responses in plants and increase shoot and/or root weight 5,[16][17][18][19][20] . In addition, microalgae extracts such as polysaccharides have proven to enhance growth of agricultural crops 13,15,21,22 . Sugars for instance act both as effective signalling molecules and as immediate substrates for intermediary metabolism, and could therefore promote plant growth and development 20,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that algal extracts and their purified compounds can induce strong physiological responses in plants and increase shoot and/or root weight 5,[16][17][18][19][20] . In addition, microalgae extracts such as polysaccharides have proven to enhance growth of agricultural crops 13,15,21,22 . Sugars for instance act both as effective signalling molecules and as immediate substrates for intermediary metabolism, and could therefore promote plant growth and development 20,23 .…”
Section: Discussionmentioning
confidence: 99%
“…This, especially, is significant information in the context of this study because buckwheat seeds contain rutin which promotes the growth of fungi [15]. Additionally, algae extracts are gaining acceptance as plant growth promoters (PGPs) as they enhance plant tolerance to a wide range of abiotic stressors and promote growth [16][17][18][19][20]. Similar effects on plants have been observed with nitrophenols [21][22][23].…”
Section: Introductionmentioning
confidence: 85%
“…Microalgae have been used in various industries, such as biofuel, cosmetics, bioremediation, and biocontrol, so we examined the application of microalgae as bioenhancers in soybean plants (Ronga et al, 2019). As shown in Fig.…”
Section: Possibility Of Microalgae As Biological Enhancersmentioning
confidence: 99%
“…(1-6) of OPR 1 has improved growth compared to control groups (1-1 and 1-2), while groups treated with the cleared solution (3-3) or spray (3-6) of OPR 3 display an improved phenotype Manuscript to be reviewed increasing yields (Ronga et al, 2019). For example, inoculation of C. vulgaris and S. dimorphus increases rice yields by improving nitrogen fixation (Garcia-Gonzalez & Sommerfeld, 2016).…”
Section: Application Of Microalgae As Biological Enhancersmentioning
confidence: 99%